Analysis of Patient Safety Implementation Using Linear Regression Test - Fanny, Nabilatul; Dyah Dewi Arini, Liss (LPPM Universitas Duta Bangsa Surakarta, 2024)
The background of this research is that interpersonal communication factors and attitudes can improve the implementation of patient safety in hospitals. The aim of this research is to analyze the influence of Interpersonal Communication and Attitudes on the implementation of Patient Safety in hospitals. Primary data was obtained through a questionnaire filled out by nurses at Jati Husada Karanganyar Regional Hospital. The sample was 31 midwives. The data from the questionnaire was then tested for linear regression at a significance level of 0.005. The results of the research show that the implementation of patient safety at RSU Jati Husada is good, 57.6% of patient safety has been implemented quite well through interpersonal communication and attitudes. Interpersonal Communication and Attitude variables have a significant influence on the implementation of patient safety at RSU Jati Husada Karanganyar. The variables Interpersonal Communication and Attitude have a significant influence on the implementation of patient safety at RSU Jati Husada, the influence is positive. Thus, the better the midwife's attitude in implementing patient safety SOPs, the higher the level of patient safety implementation.